Simulation and performance evaluation of IEEE802.11 WLAN under different operating conditions - Sara Khalaf; Hamid M. Hasan (Institute of Advanced Engineering and Science, 2022)
A wireless local area network (WLAN) based on IEEE802.11 protocol is the essential part for connection to the internet .and it is widely used in our life today and tomorrow. The growth in the number of nodes per small area likes home, office, and so on. This increase in density led to the degradation in performance in terms of throughput and delay experienced by the end-users. So many amendments proposed in order to improve the performance. Then the performance evaluation of WLAN is an important research topic. In this paper, the performance of WLAN working at 2.4GHz and 5 GHz assessed in a home-like area under the widely used applications the assessment is in terms of throughput and delay. The evaluation conducted by using the optimum networks (OPNET) 14.5 modeler simulator. In this work, we concluded that: using a single AP showed degradation in performance due to congestion. Because all nodes use the same transmission channel which showed clearly in the case of the data rate of 6 Mbps in both (a and g) standards. The effectiveness is about (1.1%, 1.3%) respectively. While using two APs improves the performance for the same case to about (28% and 65%) since it mitigates the congestion because each AP uses a different communication channel.